(untitled) (diségno, 2021)
The VII edition of the 3D Modeling & BIM Workshop - Digital Twin took place on April 14, 2021 in webinar mode, like the VI edition. The first main consideration concerns the possibility offered by the telematic link, which has become, in the last year, the most widespread communication tool, allowing the scientific communities to easily stay in touch and effectively disseminate their research. From north to south, passing through the center, the geographical location of the participants was irrelevant: there were 220 participants in the study day. This perfectly shows how, in the future, the conferences must contemplate the possibility of allowing remote connection, enabling those who are unable to move easily to participate (read more).